Crashworthiness and Deformation Pattern Analysis of Single and Double Wall with Addition Infill Structure - Bintara, Redyarsa Dharma; Choiron, Moch. Agus; Zakariya, Yahya; Shiddieqy, M. Hasbi Ash; Pratama, Fajar Adi (Universitas Negeri Malang, 2024)
Ship collisions are a phenomenon that often occurs in maritime transportation. One part of the ship that often experiences damage is the ship's wall (hull). This research aims to analyze and compare deformation patterns, stress distribution, and energy absorption in three wall models, single wall, double wall, and double wall, with the addition of infill structures. The infill structure used Polylactic Acid (PLA) polymer material because it provided convenience in the manufacturing process, while the walls of the test model used Aluminum 6063 material. The test model was developed by carrying out the design process using CAD software. Furthermore, a simulation test was carried out using software based on the finite element method with an explicit dynamic analysis type. Each test model received an impact load at a speed of 10 m/s that was carried out by the impactor. The results showed that the largest total energy absorption occurred in the double wall model with a filler structure (3643.49 J). In addition, the outward deformation pattern occurs in the double wall without a filler structure, while the inward occurs in the model with the addition of a filler structure. There were three types of stress distribution for single wall, double wall, and double wall with the addition of infill structure, namely concentrated stress, inline uniform stress, and a combination of both concentrated and inline uniform stress, respectively.